Disease and aging: what can we learn from Darwinian medicine? - Tadinac, Meri (2012)
Darwinian medicine, an attempt to understand why natural selection has left bodies vulnerable to disease and deterioration through aging, is a relatively new approach. In this lecture, divided into three parts, we will try to outline some of its basic ideas and present some empirical results obtained within this framework. In the first part we will propose some answers that Darwinian medicine offers to a puzzling question: as evolution by natural selection has shaped, over millions of years, very sophisticated bodily mechanisms, why has it not eliminated the causes of their illness and deterioration? In the second part we will present some empirical findings, obtained on the psoriasis model, concerning the concept of “allostatic overload” as a trigger for certain types of diseases, and the differences in the immune system responses to allostatic load between individuals with different behavioural strategies - hawks and doves. The third part of the lecture will outline another major interest of Darwinian medicine – the problem of senescence, a process of bodily deterioration occurring at older ages – and the idea that the maintenance of the organism after the age of reproduction is not favoured by natural selection. In summary, we will present some of the key points of the relatively new field of evolutionary medicine and its implications for the way we view, understand, and treat disease.
Projekt MZOS
ENG